Advances in Longitudinal HCI Research - Karapanos, Evangelos; Gerken, Jens; Kjeldskov, Jesper; Skov, Mikael B (Human-computer interaction series, 2021)
Longitudinal studies have traditionally been seen as too cumbersome and labor-intensive to be of much use in research on Human-Computer Interaction (HCI).However, recent trends in market, legislation, and the research questions we address, have highlighted the importance of studying prolonged use, while technology itself has made longitudinal.